The immunomodulatory activity of meningococcal lipoprotein Ag473 depends on the conformation made up of the lipid and protein moieties. - Ching-Liang Chu; Yen-Ling Yu; Yueh-Chen Kung; Pei-Yu Liao; Ko-Jiunn Liu; Yen-Tzu Tseng; Yuan-Chuen Lin; Steve Shih-Yang Hsieh; Pele Choi-Sing Chong; Chiou-Ying Yang (PLoS ONE, 2012)
We have previously demonstrated that the meningococcal antigen Ag473 in the presence of Freund's adjuvant can elicit protective immune responses in mouse challenge model. In this study, we evaluated the structural requirement for the immunological activity and the possible signaling pathway of recombinant Ag473 antigen produced in E. coli. We found that lipidated Ag473 (L-Ag473) possesses an intrinsic adjuvant activity that could be attributed to its ability to activate dendritic cells and promote their maturation. In addition, we found that L-Ag473 can activate human monocytes and promote maturation of human monocyte-derived dendritic cells. These results provide an indirect support that L-Ag473 may also be immunogenic in human. Interestingly, the observed activity is dependent on the overall conformation of L-Ag473 because heating and proteinase K treatment can diminish and abolish the activity. Furthermore, our data suggest a species-differential TLR recognition of L-Ag473. Overall, these data suggest a new paradigm for the ligand-TLR interaction in addition to demonstrating the self-adjuvanting activity of the vaccine candidate L-Ag473.